Two-Photon and Multicolor Fluorogenic Bioorthogonal Probes Based on Tetrazine-Conjugated Naphthalene Fluorophores - Kim, Dahham; Lee, Jae Hong; Koo, Ja Young; Kim, Hwan Myung; Park, Seung Bum (Bioconjugate Chemistry, 2020)
Herein, we report the use of two-photon fluorogenic probes using tetrazine-based bioorthogonal reactions with multicolor emissions that cover nearly all of the visible region. New fluorogenic probes were designed based on donor-acceptor-type naphthalene structures conjugated with a fluorescence-quenching tetrazine moiety for turn-on properties in one- and two-photon fluorescence. Our fluorescent probes showed a moderate to good turn-on ratio after bioorthogonal inverse electron demand Diels-Alder cycloaddition with trans-cyclooctenol in one- and two-photon fluorescence. We successfully applied our probes to mitochondria- and lysosome-selective bioorthogonal imaging in live cells with one-/two-photon and one-photon microscopy, respectively.
Keywords: Bioorthogonal reactions; Fluorogenic probes; Fluorogenics; Multi-color emissions; Multi-colors; Probe-based; Tetrazines; Two photon; Two photon fluorescence; Visible region; Cell Line, Tumor; Cycloaddition Reaction; Fluorescent Dyes; Heterocyclic Compounds; Humans; Microscopy; Naphthalenes; Photons